DIVORCE BEYOND THE COURT OF RELIGION FOR HIGHER EDUCATION (GRADUATE) - Yanti Yanti (Universitas Islam Negeri (UIN) Mataram, 2020)
The background in this study is divorce outside the Religious Courts conducted by couples who have a history of higher education (bachelor). In-Law Number 1 of 1974 Article 39 and Compilation of Islamic Law Article 115 which states that